Modelling dynamics of social support networks for mutual support in coping with stress - Ab. Aziz, Azizi; Treur, Jan (2009)
This paper presents a computational multi-agent model of support receipt and provision to cope during stressful event within social support networks.The underlying agent model covers support seeking behavior and support provision behaviour. The multi-agent model can be used to understand human interaction and social support within networks, when facing stress.Simulation experiments under different negative events and personality attributes for both support receipt and provision pointed out that the model is able to produce realistic behavior to explain conditions for coping with long term stress by provided mutual support.In addition, by a mathematical analysis, the possible equilibria of the model have been determined.